Electric Vehicle Charging landscape aiming for Self Reliant India - Pradhan, Priyabrata (PREPARE@u® | IEI Conferences, 2021)
– One of the revolutionizing global strategies for the de-carbonization of the transport sector is the transition to electric mobility. India is amongst the few countries that propagate the global EV30@30 campaign, targeting to have at least 30% new electric vehicles by the year 2030. An essential pre-requisite to achieve this ambitious transition comprises of accessible & robust network of electric vehicle (EV) charging infrastructure for which the Government of India has enabled various policies to promote the development of the charging network. However, in view of the present scenario of this new infrastructure type, there is a need for customizing to the Indian transport system along with building capacity among stakeholders to support the on-ground expansion. This paper aims at giving the efficient & timely implementation of electric vehicle charging structure ensuring proper integration of transportation & supply networks.